SimpleSim: An Open-Source Python Simulator for SDM-EON Resource Allocation - Oliveira, Ramon A.; Oliveira, Helder (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Space-Division Multiplexing Elastic Optical Networks (SDM-EONs) increase transmission capacity while significantly raising the complexity of the Routing, Modulation, Spectrum, and Space Allocation (RMSSA) problem set, demanding flexible simulation environments for evaluation. This paper presents SimpleSim, an open-source Python-based discrete-event simulator for prototyping and benchmarking RMSSA strategies in SDM-EONs. The tool adopts a modular architecture with external XML-based topology definition, integrates widely used scientific libraries, and provides automated statistical analysis with confidence intervals and built-in plotting capabilities. SimpleSim supports multi-core fiber modeling, crosstalk-aware allocation, and comparative evaluation of resource allocation algorithms under configurable traffic loads.